صيغة أفعل في سورة البقرة ودلالتها: دراسة وصفية تحليلية / The Scale of Af’ala in Surah Al Baqarah and Their Meanings - Hasyim Ashari (Jurusan Bahasa dan Sastra Arab Universitas Islam Negeri Alauddin Makassar, 2020)
The verb with a scale of af’ala is a form of the verb in Arabic that obtains additional letters, and has various meanings including al-ta’diyyah, which is changing the verb from one that doesn’t need an object to a verb that requires an object, or from verb that requires one object to a verb that requires two objects. Another meaning of the verb with a scale of af’ala is al-sayrurah, which is to make something to have new aspects. And this paper aims to detect the presence of a verb with a scale of af’ala in surah al-Baqarah by explaining its meaning based on the opinions of interpreters and language experts, and further detecting whether the interpreters think that these meanings are carried by the letter of hamzah, or from new forms of words. The method used is a descriptive analysis approach. The author found that there are a number of verbs in surah al-Baqarah with a scale of af’ala, and they are dominated by the meaning of al-ta’diyyah, while the rest have the meaning of al-sayrurah, and some have the same meaning before the verbs obtaining added hamzah. It is also found that some interpreters consider these meanings carried by the letter of hamzah, and some sometimes consider new forms of words that carry these meanings.Keywords: Scale of Af’ala, al-Ta’diyyah, al-Sayrurah, Surah al-BaqarahAbstrakKata kerja dengan timbangan af’ala merupakan salah satu bentuk kata kerja di dalam bahasa Arab yang mendapatkan huruf tambahan, dan memiliki beragam makna di antaranya al-ta’diyyah yaitu merubah kata kerja dari yang tidak membutuhkan objek menjadi kata kerja yang membutuhkan objek, atau dari yang membutuhkan satu objek menjadi kata kerja yang membutuhkan dua objek. Makna lain dari kata kerja dengan timbangan af’ala adalah al-sayrurah yaitu menjadikan sesuatu memiliki hal baru. Dan tulisan ini bertujuan untuk mendeteksi adanya kata kerja dengan timbangan af’ala di dalam surah al-Baqarah dengan menjelaskan maknanya berdasarkan pendapat para ahli tafsir dan bahasa, dan selanjutnya mendeteksi apakah para ahli tafsir menganggap bahwa makna-makna tersebut dibawa oleh huruf hamzah, atau berasal dari bentuk kata baru. adapun metode yang digunakan adalah pendekatan deskriptif analisis. Dan penulis menemukan bahwa sangat banyak kata kerja di dalam surah al-Baqarah dengan timbangan af’ala, dan mayoritas mengandung makna al-ta’diyyah, sedangkan selebihnya bermakna al-sayrurah, dan ada pula yang maknanya tetap sama sebelum kata kerja tersebut mendapatkan tambahan hamzah.Dan ditemukan juga bahwa sebagian ahli tafsir menganggap makna-makna tersebut dibawa oleh huruf hamzah, dan sebagian lagi terkadang menganggap huruf hamzah dan terkadang menganggap bentuk baru dari kata yang membawa makna-makna tersebut.